A study of Thumos in early Greek epic - Caswell, Caroline P. (Mnemosyne, Supplements, 1990)
The language of early Greek epic, exemplified primarily by Homer, contains numerous descriptions of inner states and uses a specific vocabulary to do so. Scholars understand these descriptions in a general way; but the precision of the expressions remains a mystery. In this work, one of the most important of these words, thumos , is examined in each of its contexts. This synchronic formulaic analysis is carried out according to the contexts of thumos : the cognitive/intellectual, the emotional, and the physical. Two additional contexts, deliberation and motivation, are discussed separately. Within the discussion of each context, the functional synonyms of thumos, particulary phren/phrenes , and other frequent associates of thumos , are examined. Thumos has associations with words relating to winds and storms, a fact which helps clarify its significance in all contexts. Because this work is a discussion of thumos in all contexts, and also contains an appendix of the relevant passages, it should be useful to scholars engaged in research on Homeric vocabulary.